Liver resection for non-colorectal metastases - Schwarz, Christoph (Eur Surg, 2018)
Whereas liver resection for colorectal metastasis has become standard of care, hepatectomy in patients with non-colorectal metastases remains controversial, mainly due to a heterogeneous tumor biology and missing data from prospective trials. This review aims at giving an overview about the indications and limits of liver surgery in patients with an advanced disease of a non-colorectal malignancy. Even though prospective trials are largely missing, results from retrospective studies indicate a survival benefit for liver resection in selected patients. Thus, in metastasized patients, treatment strategies should be developed in a multidisciplinary tumor board including an experienced liver surgeon.